Implementation Of Servqual To Improve Customer Satisfaction And Loyalty: B2B Marketing At PT. Migas Mandiri Pratama Hilir - Azka Syandria Sekar Maheswari; Anas Hidayat (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze how the application of SERVQUAL in improving customer satisfaction and loyalty in the context of B2B services at PT. Migas Mandiri Pratama Hilir. The object of this study is the fuel transportation service provided by the company. The study uses a qualitative approach with data collection methods through questionnaires, in-depth interviews, and observations. The sample consists of 20 respondents who are clients of the company. The results of the study indicate that dimensions of service quality, such as reliability and responsiveness, play a significant role in creating customer satisfaction and loyalty. Despite operational challenges, such as losses during shipping and poor road conditions, strong relationships with customers and on-time delivery strengthen loyalty. The managerial implications of this study are the importance of improving service quality and communication to maintain customer loyalty.